Desenvolvimento de cultivares de couve-flor em função de telas de sombreamento e épocas de cultivo - Bortoluzzi, Filipe Mizobe (2018)
The main factor for the development of cauliflower is temperature. To minimize this effect, it is necessary to identify strategies that alter environmental conditions, such as the use of shading screens. The objective of this work was to evaluate the development under protected and field cultivation in two seasons for cauliflower cultivation under tropical edaphoclimatic conditions. The experimental design was the completely randomized (DIC) in 5x2 subdivision plots (five environments and two growing seasons), with three replications. The number of leaves, leaf area, plant diameter, leaf dry mass, stem and total, relative growth rate, absolute growth rate, net assimilatory rate, growth rate of the cultivars Verona CMS, Cindy and Sharon were evaluated leaf area index, leaf area ratio, leaf area ratio, fresh mass of the inflorescence, and productivity. In order to grow Verona CMS, productivity in the first season was higher than the second season, with higher yields for the Sombrite 50% (35.33 ton ha-1 ) and Chromatinet (31.33 ton ha-1 ) screens. In the second season there was no variation between treatments. In order to cultivate Cindy, productivity in the first season was higher than the second season, with higher yields for the Sombrite 50% (31.66 ton ha-1 ) and Sombrite 35% (27.66 ton ha-1 ) screens. In the second season there was no variation between treatments. In order to cultivate Sharon, productivity in the first season was higher than the second season, however, without significant variation between the screens. In the second season there was also no variation between treatments. It is concluded that the use of screens does not influence the increase of productivity of Sharon cultivar. It is concluded that the screens 50% Sombrite and 35% Sombrite, to cultivate Verona CMS, provide an increase in cauliflower productivity in the first season. In cultivation of second season the use of screens does not interfere in the production of cauliflower. To grow Cindy, the screens of Sombrite 50% and Chromatinet provide an increase in cauliflower productivity in first season. In cultivation of second season the use of screens does not interfere in the production of cauliflower. For Sharon, the use of screens does not influence the productivity increase of Sharon cultivar